PENERAPAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA - Dindin Sutrisna (Balai Diklat Keagamaan Bandung, 2023)
Mathematical instruction at MTsN 5 continues to employ traditional methods, in which the dominant teacher actively imparts knowledge via the lecture method. Students are not actively engaged, they listen, write, and take notes, so that learning mathematics becomes monotonous and makes them difficult to comprehend the material. Classroom Action Research (CAR) was conducted using a mathematically realistic approach. How are the activities and learning outcomes using a realistic mathematics approach? This research method employs classroom action research which consists of a series of stages beginning with planning, action, observation, and reflection. Observation guidelines, field notes, interview sheets, final evaluation, and student worksheets were utilized for data collection. The data were analyzed and reflected using qualitative methods, whereas numerical data were processed using quantitative methods. Students who were initially less enthusiastic and less active were able to alter their attitude patterns and become enthusiastic, active, and full of confidence. The findings can be seen from student learning activities, particularly in discussions that are quite good. There is cooperation, exchanging ideas, explaining to each other (peer tutors), mutual support and task sharing in groups, responsibility in problem-solving, and critical thinking. They are not awkward to argue with group members or with other groups as well. To sum up, student achievement in learning Mathematics using a realistic mathematics approach has increased significantly in each cycle.